2020
DOI: 10.3892/mco.2020.2186
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of single‑port vs. multi‑port surgery for rectal cancer

Abstract: The aim of the current systematic review was to compare the short-term clinical and oncological outcomes of single-port surgery (SPS) to multi-port surgery (MPS) for rectal cancer in MEDLINE, PubMed and Cochrane Library from January 2010 to December 2018. A total of 5 clinical controlled studies composed one randomized pilot study and four non-randomized studies with a total of 461 patients were analyzed after a systematic review. A total of 125 patients (27.1%) underwent SPS and 336 patients (72.9%) underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…22 Furthermore, SPS can provide more oncological outcomes in the patients with colon cancer. 23 On the other hand, there are some reports of the use of SPS for rectal surgery, 24 and a recent systematic review has reported that SPS can also be performed safely and provide good shortterm oncological outcomes. 25 However, the usefulness of SPS, including long-term oncological outcomes, is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…22 Furthermore, SPS can provide more oncological outcomes in the patients with colon cancer. 23 On the other hand, there are some reports of the use of SPS for rectal surgery, 24 and a recent systematic review has reported that SPS can also be performed safely and provide good shortterm oncological outcomes. 25 However, the usefulness of SPS, including long-term oncological outcomes, is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with previous systematic reviews on SILS and CMLS in the treatment of CRC [13,14] , the greatest feature of this study is that the 8 included articles were all high-quality RCT studies, from different countries and regions of the East and West, with some representativeness, of which 5 were registered for clinical trials, so the results had high reliability. The limitations of this study are mainly the lack of long-term follow-up results in the included literature, including local tumor recurrence or distant metastasis rate, survival rate, etc., which cannot evaluate the long-term efficacy of SILS in the treatment of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…After more than 10 years of development, SILS has been widely used in the treatment of CRC [11] . However, there is still a lack of high-quality evidence-based medical evidence for the safety and efficacy of SILS in the treatment of CRC compared with CMLS, and some previous meta-analyses included too many retrospective non-randomized studies [12][13][14] , resulting in poor reliability and stability of this result. Therefore, the main purpose of this study is to systematically evaluate the published high-quality RCT of SILS and CMLS in the treatment of CRC to objectively evaluate the safety and efficacy of SILS in CRC surgery.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, SPL is considered a more demanding approach, not suitable for every intervention as it largely depends on the available working space [ 19 ]. With the introduction of systems like da Vinci SP, single-port interventions still lag behind the operations performed using multi-port robotic systems [ 13 , 29 ].…”
Section: Introductionmentioning
confidence: 99%